Gingerbread cookie murder ebook - Fluke, Joanne (Hannah Swensen Mystery, 2010)
New York Times -bestselling authors: This merry collection of holiday mysteries is " a yuletide whodunit treat" ( Publishers Weekly ). This collection of three novellas by much-loved mystery authors is perfect for spicing up the season: Gingerbread Cookie Murder by Joanne Fluke When Hannah Swensen finds her neighbor on the floor of his condo with his head bashed in—next to an upended box of Hannah's Gingerbread Cookies—she discovers a flurry of murder suspects that's as long as her holiday shopping list. The Dangers of Gingerbread Cookies by Laura Levine Jaine Austen has been enlisted to help with her parents' retirement community's play The Gingerbread Cookie That Saved Christmas . Playboy Dr. Preston McCay is playing the role of the gingerbread cookie when he "accidentally" falls to his death during the final act. Now Jaine must figure out if one of the doctor's jealous lovers was capable of murder. Gingerbread Cookies and Gunshots by Leslie Meier When Lucy Stone discovers the body of a man whose five-year-old son, Nemo, disappeared, she senses foul play. Crumbs from a gingerbread cookie Lucy gave to Nemo are found in the back seat of the victim's car. With the hours quickly ticking till Christmas, Lucy races against the clock to find a killer before he strikes again. Includes over 10 luscious holiday recipes!